Pengaruh Persepsi Masyarakat Terhadap Covid-19 Dan Perilaku Penerapan Protokol Kesehatan Berdasarkan Health Belief Model - Putri, Stevani Dinda; Wijono, Heru; Boengas, Sawitri (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2023)
COVID-19 is a disease caused by SARS CoV-2, which causes many deaths. The government launched the 5M health protocol to reduce morbidity and mortality from COVID-19. Awareness of implementing health protocols is influenced by various factors besides knowledge. Theory Health Belief Model (HBM) focuses on individual perceptions and beliefs about the COVID-19 which includes which perceived susceptibility, perceived severity, perceived benefits, and perceived barriers, can be used in predicting public awareness in carrying out the behavior of implementing the COVID-19 health protocol. This study aims to determine the relationship between perceived vulnerability, perceived severity, perceived benefits and perceived obstacles with adherence to implementing the COVID-19 health protocol. This research is an analytic observational study, the data was taken by cross-sectional use google form. Correlation test was performed with Rank Spearman test use SPSS version 25. Results: There were 40 respondents, 21 (53.5%) female, 19 (47.5%) male, 17 to 70 yo. There is a significant relationship between perceived severity (p = 0.003), perceived benefits (p = 0.000) and perceived barriers (p = 0.004) to the behavior of implementing health protocols, but no relations was found between perceived susceptibility (p =0.216) and behavior of implementing protocols health. Perceived severity, perceived benefits, and perceived barriers are related to the behavior of implementing health protocols